Ziritaxestat Drug–Drug Interaction with Oral Contraceptives: Role of SULT1E1 Inhibition. Issue 4 (12th July 2022) - Helmer, Eric; Karimian, Negin; Van Assche, Karen; Seghers, Ineke; Le Tallec, Sandrine; Cherala, Ganesh; Scott, Graham; Namour, Florence S.
Abstract : In vitro signals indicate that ziritaxestat is a weak cytochrome P450 (CYP) 3A4 inhibitor and inducer. Therefore, potential drug–drug interactions (DDIs) with oral contraceptives were examined at a time when ziritaxestat was under development for treatment of fibrotic diseases. This open‐label, crossover (fixed sequence) DDI study enrolled healthy, nonpregnant women aged 18–65 years ( n = 15) who were using highly effective contraception, such as a nonhormonal intrauterine device, bilateral tubal occlusion, or sexual abstinence. A single dose of oral contraceptive (0.03 mg ethinyl estradiol (EE) and 3 mg drospirenone (DRSP)) was administered on days 1, 8, and 18, and ziritaxestat 600 mg once daily was administered from days 8 to 23. Co‐administration resulted in a 2.8‐fold and 2.4‐fold increase in EE maximum plasma concentration (Cmax ) and area under the plasma drug concentration–time curve from time zero to infinity (AUC0–inf ), respectively (day 18 vs. day 1). DRSP Cmax and AUC0–inf increased by 1.1‐fold and 1.2‐fold, respectively. DRSP is a CYP3A4 substrate, meaning increased EE exposure with ziritaxestat was not due to CYP3A4 inhibition. Ziritaxestat inhibition of EE glucuronidation and sulfation was quantified by liquid chromatography with tandem mass spectrometry in day 1 and day 18 plasma samples after EE conjugate hydrolysis. The ratio of EE AUC from time of administration up to the time of the last quantifiable concentration (AUClast ) with/without hydrolysis by arylsulfatase was substantially lower on day 18 vs. day 1, suggesting ziritaxestat is a potent inhibitor of sulfation; EE glucuronidation was largely unaffected by ziritaxestat. In vitro assessment confirmed ziritaxestat is a potent inhibitor of sulfotransferase family 1E member 1 (half‐maximal inhibitory concentration < 0.8 μM). These findings highlight the importance of assessing enzymes other than CYP3A4 when investigating potential DDIs with oral contraceptives.